A numerical and experimental study of internal solitary wave loads on semi-submersible platforms. (15th February 2018) - Wang, Xu; Zhou, Ji-Fu; Wang, Zhan; You, Yun-Xiang
Abstract: Using a double-plate wave maker, a series of laboratory experiments of internal solitary wave (ISW) loads on semi-submersible platforms were conducted in a density stratified fluid tank. Combined with experimental results, a numerical flume based on the Navier-Stokes equations in a two-layer fluid is developed to simulate nonlinear interactions between ISWs and a semi-submersible platform. The numerical results of horizontal and vertical forces, as well as torques on the semi-submersible platform also agree well with the experimental measurements. Besides, the numerical results indicate that the horizontal and vertical forces on the semi-submersible platform due to ISWs can be divided into three components, namely the wave pressure-difference forces, viscous pressure-difference forces, and the frictional force which is negligible. For the horizontal force, the wave and viscous pressure-difference components are of the same order, implying that the viscous effect is significant. For the vertical force, the contribution of the viscous pressure-difference is not important. Moreover, the diffraction effect is significant for horizontal force and insignificant for vertical force. Hence, it is feasible to estimate the vertical load using the Froude-Krylov approach. Highlights: We investigated the characteristics of internal solitary wave loads on the platform via experiments and simulations. For the horizontal force, the viscous effect is significant, while it's not important for the vertical force. It is feasible to estimate the vertical load induced by an internal solitary wave by the Froude-Krylov approach.